2021
DOI: 10.1063/5.0061770
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast vibrational dynamics of a solute correlates with dynamics of the solvent

Abstract: Two-dimensional infrared (2D-IR) spectroscopy is used to measure the spectral dynamics of the metal carbonyl complex cyclopentadienyl manganese tricarbonyl (CMT) in a series of linear alkyl nitriles. 2D-IR spectroscopy provides direct readout of solvation dynamics through spectral diffusion, probing the decay of frequency correlation induced by fluctuations of the solvent environment. 2D-IR simultaneously monitors intramolecular vibrational energy redistribution (IVR) among excited vibrations, which can also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 77 publications
2
7
0
Order By: Relevance
“…Figure 5, top, shows the GP population for acetonitrile (blue crosses), modeled by a biexponential decay convoluted with a Gaussian function (blue solid line). The GP population decay is observed to be well captured by this biexponential fit, with the two time constants being 0.4(1) ps and 38 (6) ps. The population of NG (filled dots) survives for the time scales investigated here.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Figure 5, top, shows the GP population for acetonitrile (blue crosses), modeled by a biexponential decay convoluted with a Gaussian function (blue solid line). The GP population decay is observed to be well captured by this biexponential fit, with the two time constants being 0.4(1) ps and 38 (6) ps. The population of NG (filled dots) survives for the time scales investigated here.…”
mentioning
confidence: 76%
“…Ultrafast photoinduced chemical reactions in solution and condensed-phase environments are the underlying phenomena for many processes, e.g., for photosynthesis and vision in biological systems as well as for photocatalysis and for dye-sensitized solar cells. Despite the importance of such reactions, the influence of the solvent environment on structural dynamics in solution-phase reaction is not yet fully understood. Solvent–solute interactions are known to affect the potential energy landscapes, a phenomenon which can be experimentally observed e.g., by shifts in absorption spectra and changes in lifetimes of different electronic states as a function of solvent type. The solvent is therefore also expected to influence the earliest dynamics in solution-phase reactions, fundamentally impacting their course. To understand the solvent effect on the subpicosecond reaction events, the direct observation of reactions on these time scales is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, dual-frequency strategies 107 using the C≡N/N3 and imido (~1730 cm -1 ) modes as reporters could provide insight into the rates of intramolecular vibrational energy redistribution (IVR) in each PhENR variant, as well as how it depends on intramolecular coupling 82 and perturbations by bath modes. 25 As research progresses, will explore how the spatial distribution of label dynamics/disorder in PhENR varies as a function of FMN redox state, mutations, protein concentration, 57,58,89,110 pressure and temperature, 61,63,111 and solvent composition. 41,42,44,54,111 We will also explore communication between active site dynamics and fluctuations at distal sites 12 by employing genetically-encoded labels in addition to inhibitors and substrate analogs.…”
Section: Discussionmentioning
confidence: 99%
“…23 2D IR studies of small molecules and metal complexes in solution have provided insight into effects of viscosity on isomerization 24 as well as possible relationships between short-timescale equilibrium dynamics and energy transfer in reactivity. 25,26 For enzymes and other macromolecules, vibrational probes that absorb in a 'transparent window' of the mid-IR spectrum are attached to amino acid side chains, reactive cofactors, or substrate/TS analogs. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] Frequency fluctuation correlation functions (FFCFs) extracted from spectral diffusion measurements provide detailed descriptions of the timescales and magnitudes of local fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Vibrational relaxation and thermalization in molecules occur via an intramolecular vibrational energy redistribution (IVR) process, which has been studied using a variety of experimental methods. Energy transfer and thermalization in covalent networks is better understood than the transfer across a metal center in a transition-metal complex for which only a few studies were reported. The coordination bonds at the metal center are often weak resulting in very inefficient energy transfer across the metal. For example, the lifetime of CO stretching modes in some metal carbonyls reaches 1 ns. A similar situation is encountered when an organic compound is attached to a metal or semiconductor surface. The surface binding energy is often small resulting in weak thermal conductivity through the interface. In contrast to surfaces, transition-metal complexes feature high-frequency vibrational modes on each side of the metal atom, which can potentially participate in the exchange of high-frequency quanta across the metal center.…”
Section: Introductionmentioning
confidence: 99%